Evolution of the burden of disease for high BMI-associated colorectal cancer, 1990–2021: Global trends, regional heterogeneity, and population risk stratification - Guangyi zhu; Yilan Sun; Dongbo Lian; Buhe Amin; Guangzhong Xu; Jing Wang; Nengwei Zhang; Dezhong Wang (Preventive Medicine Reports, 2025)
Objective: Quantify global high body mass index (BMI)-linked colorectal cancer death and disability-adjusted life years (DALYs) (1990–2021) using the Global Burden of Disease (GBD) 2021 data, assessing spatiotemporal trends to inform prevention strategies. Methods: Geographic analysis, age-sex stratification, and sociodemographic index (SDI) quintiles evaluated disease distribution. Calculated estimated annual percentage change (EAPC) for trends. Demographic decomposition models quantified the contributions of population aging, epidemiological changes, and growth. Assessed health inequality via the slope inequality index (SII) and concentration index and prevention efficiency with SDI-age-standardized DALYs rate frontier. Results: Globally from 1990 to 2021, deaths from high BMI-associated colorectal cancer rose from 41,536 to 99,268, with the age-standardized death rate increasing from 1.14 to 1.17. The age-standardized death rate significantly increased in low- and middle-SDI regions while declining in high SDI regions. Disease burden growth was prominent in East and Southeast Asia. Death rates and rates of DALYs were higher in men than in women, and the burden was highest in people aged 60 years or older. Population growth was the primary driver of the increased burden (contributing >60 % to deaths and DALYs), followed by population aging. While health inequality (as measured by the SII) slightly decreased from 42.12 to 39.76, significant socio-demographic disparities persisted. Conclusion: High BMI-associated colorectal cancer burden escalates in low-middle SDI regions and elderly males. Targeted prevention and healthcare efficiency in low SDI areas are critical.